The Civil War in Southern Sudan and Its Effect on Youth and Children - Melha Rout Biel (Social Work and Society)
The Civil War in Sudan, which began in June 1983, has caused a numbers of social, cultural and economical problems for Sudan. Many social changes took place, not only in the southern Sudan, where the war has been fought since its inception, but also in the Sudanese Nation as a whole. In this contribution, I would like to give a short summary about the effect of the war on the Sudanese society, in general, and on youth and children, in particular. This is important, because youth and children are the future of every nation. Because the youth and children in southern Sudan are gravely affected by the current war, this article will specifically address these effects. Youth and children in the North of the country are, however, almost equally affected by the conflict. After discussing historical background of Sudan and its political and developmental condition, I will briefly summarize the social situation and the role of social work in Sudan during and after the conflict.